3D compression–torsion cubic mechanical metamaterial with double inclined rods. (May 2020) - Wang, Liang; Liu, Hai-Tao
Abstract: A novel 3D compression–torsion cubic mechanical metamaterial (CTCMM) with double inclined rods is proposed converting axial compression into a torsion. The CTCMM under uniaxial compression is studied by theoretical analysis, experiments and numerical simulations. The relationships between relative densities and geometric parameters are analyzed to meet the needs of lightweight. Based on the derivation of the over-deformation mechanism, the torsion angle is derived by the Timoshenko beam theory. The arrangements of gradient models are designed and fabricated by 3D printing, as the specimens for static compression experiments. Results show that the torsion angles of the numerical and experimental results agree well with the theoretical solution. Moreover, the proposed CTCMM possesses a similar compression–torsion effect compared to previously reported 3D CTCMM. Meanwhile, the improved 3D CTCMM with the better compression–torsion effect is proposed, compared with the original structure, the different phenomenon wherein the torsion angle first increases and then declines. Finally, cell number, variable cross-section and perforated plates all affect the compression–torsion effects of 3D CTCMM. The above research provides a new idea for improving the performance of CTCMM, no longer limited to the deformation mode of a single inclined rod.